Pendampingan Sumber Daya Manusia di TPQ Hidayatul Islam Dusun Seglagah Desa Sempu Kecamatan Ngebel - Sulis Binti Munfaati; Ahmad Syafi’i (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study aims to describe the process and outcomes of human resource assistance at TPQ Hidayatul Islam, Seglagah Hamlet, Sempu Village, Ngebel Subdistrict. The background of this activity is the limited quality and quantity of educators, which affects the effectiveness of Qur’anic learning. The research employed a descriptive qualitative approach through observation, interviews, and documentation during the mentoring process. The findings indicate that the assistance improved the competence of teachers in terms of mastering Qur’anic teaching methods, classroom management, and motivation in teaching. In addition, the mentoring program increased community participation in supporting the sustainability of TPQ. The implication of this research highlights the importance of continuous assistance programs to strengthen human resource capacity, enabling TPQ to optimize its role in realizing the goals of Islamic education at the community level.